2008
DOI: 10.1111/j.1540-8167.2008.01228.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Endomyocardial Biopsy Guided by Electroanatomic Voltage Mapping in Arrhythmogenic Right Ventricular Cardiomyopathy/Dysplasia

Abstract: The results of our study (1) confirm the high diagnostic sensitivity of RV voltage mapping in patients with overt ARVC/D, (2) document a high prevalence of RV low-voltage areas even in patients with suspected ARVC/D, and (3) demonstrate that in patients with clinical evidence or suspicion for ARVC/D, presenting RV low-voltage areas, EMB guided by voltage mapping may provide ARVC/D diagnosis confirmation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
73
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(75 citation statements)
references
References 22 publications
1
73
0
1
Order By: Relevance
“…These rates are in line with those observed in a recent large two-centers study including 755 procedures (right, left and biventricular endomyocardial biopsy) and reporting a major and minor complication rate of 0.82% and 5.1% respectively for right ventricular endomyocardial biopsy (Yilmaz et al, 2010). In literature another study in which 3D-EAM-guided endomyocardial biopsy was performed in 22 patients, reported a higher rate of major complications (1.1%) and minor complications (5.7%), thus suggesting that the expertise of the operators besides the clinical condition and the underlying disorder may influence the safety of the procedure (Avella et al, 2008).…”
Section: Safetymentioning
confidence: 99%
“…These rates are in line with those observed in a recent large two-centers study including 755 procedures (right, left and biventricular endomyocardial biopsy) and reporting a major and minor complication rate of 0.82% and 5.1% respectively for right ventricular endomyocardial biopsy (Yilmaz et al, 2010). In literature another study in which 3D-EAM-guided endomyocardial biopsy was performed in 22 patients, reported a higher rate of major complications (1.1%) and minor complications (5.7%), thus suggesting that the expertise of the operators besides the clinical condition and the underlying disorder may influence the safety of the procedure (Avella et al, 2008).…”
Section: Safetymentioning
confidence: 99%
“…Ранее было показано, что при вольтажном карти-ровании ПЖ, ЭМБ из зон низкоамплитудной актив-ности позволяет значительно чаще выявлять измене-ния, в т. ч. ассоциированные с АДПЖ [3]. Однако картирование всей поверхности ПЖ является тру-доёмким, а отсутствие визуализации биотома на трех-мерных электроанатомических моделях не позволяет проводить абсолютно точное взятие фрагментов ткани.…”
Section: "прицельная" эндомиокардиальная биопсия в диагностике аритмоunclassified
“…A detailed RV endocardial voltage map is created in sinus rhythm using the standard 0.5-1.5 mV voltage cutoffs to define the endocardial substrate as previously discussed [13,22] . Special attention is focused on the periannular area and any identified low-voltage areas to ensure adequate sampling has occurred [23][24][25] . Occasionally, it can be technically challenging to perform catheter manipulation in the periannular tricuspid valve region.…”
Section: Disease Progressionmentioning
confidence: 99%